Radiological markers of neurological manifestations of post-acute sequelae of SARS-CoV-2 infection: a mini-review - Cull, Olivia; Al Qadi, Lina; Stadler, Josiane; Martin, Mykella; El Helou, Antonios; Wagner, Jeffrey; Maillet, Danica; Chamard-Witkowski, Ludivine (Frontiers in Neurology, 2023)
Neurological post-acute sequelae of COVID-19 (Neuro-PASC) is a rising concern among medical professionals, as patients continue to experience symptoms after they recover from COVID-19. The gap in knowledge on how COVID-19 affects the brain limits the development of effective prevention and treatment strategies. This mini-review aims to explore imaging techniques available for measuring Neuro-PASC. Searches yielded 38 articles on brain imaging techniques, including structural MRI (magnetic resonance imaging), functional MRI, diffusion MRI, susceptibility-weighted imaging, SPECT (single-photon emission computed tomography) imaging, and PET (positron emission tomography) imaging. We also discuss the optimal usage, limitations, and potential benefits of these techniques. Findings show that various cerebral imaging techniques have been evaluated to identify a reliable marker for Neuro-PASC. 18F-FDG-PET/CT and functional MRI have demonstrated hypometabolism in cerebral regions that are directly linked to patient symptoms. Structural MRI studies have revealed infarcts, white matter atrophy, and changes in grey matter volumes. One SPECT imaging study noted frontal lobe hypometabolism, while diffusion MRI showed increased diffusivity in the limbic and olfactory cortical systems. Sequence SWI showed abnormalities in white matter near the grey-white matter junction. A study on 18F-amyloid PET/CT found amyloid lesions in frontal and anterior cingulate cortex areas, and arterial spin labeling (ASL) found hypoperfusion in the frontal lobe. While accessibility and cost limit the widespread use of 18F-FDG-PET/CT scans and structural MRI, they seem to be the most promising techniques. SPECT, SWI sequence, and 18F-amyloid PET/CT require further investigation. Nevertheless, imaging remains a reliable tool for diagnosing Neuro-PASC and monitoring recovery.